Persiapan Uji Kompetensi Bidan sebagai Exit Exam - Rahmah Fitria; Joserizal Serudji; Lisma Evareny (Universitas Batanghari Jambi, 2019)
The objective of this study was to improve the quality of midwives in Indonesia through National midwife examination to answer the internal and global challenges of health higher education. Accreditation of tertiary education and the passing rate of low midwife's competency test with low minimum standard values can not answer the challenges. Researcher want to see how the phenomenon of midwife's competency test that is focused on the preparation. This research used qualitative design with a phenomenological approach. Data collection is taken through informants related to in-depth interviews, observation and document studies. Taking informants using the snowball sampling technique. The process of data analysis refers to the constant comparative method. The research shows that national midwife examination is currently not yet as the exit exam. The participant's preparation was problem resolved training and did try out. The school is contributed in early introduce the type of questions to students, tutoring, facilitation of try out and making questions but have not been carried out optimally and directed. Organizing national committees, preparation of questions, funding sources and preparation for the implementation of examinations are in accordance with the guidelines. Retaker is a problem that must be sought by all relevant parties regarding the issue of guidance and who is responsible. To answer the existing problems, it is better for national midwife examination to start as an exit exam and do “sit together” to discuss the development efforts of national midwife examination in Indonesia, including the problem of retaker.